Aktivitet som sjukdomsmarkör på kalvar i gruppsystem - Jonasson, Karin (2009)
Since long, Sweden has had exceptionally low calf mortality compared to most other countries. The tradition has been to keep calves in individual pens. With increasing number of cows per herd there is now a larger interest in more efficient and economical group systems for housing calves. However it has been noticed that bigger herds have more health problems and higher calf mortality than smaller herds. The early signs of disease are harder to detect when the animals are not fed manually. Studies show that the health of the calves influences how productive and healthy they become as cows. The health of calves has therefore become more important and there is a need for systems that can help detecting diseases among calves.